The use of a polycaprolactone-tricalcium phosphate scaffold for bone regeneration of tooth socket facial wall defects and simultaneous immediate dental implant placement in Macaca fascicularis - Goh, Bee Tin (2014)
Bone regeneration and aesthetic outcomes may be compromised when immediate implants are placed at extraction sites with dehiscence defects. The aim of this study was to compare, in a monkey model, peri-implant bone regeneration and implant stability after immediate implant placement into tooth sockets with facial wall defects in two treatment groups. In eight control monkeys, the bony defect was reconstructed with autogenous particulate bone, whereas in 10 test monkeys a polycaprolactone–tricalcium phosphate (PCL–TCP) scaffold was used. The monkeys were sacrificed after 6 months and the specimens were analyzed by histology and histomorphometry. Better maintenance of facial bone contour was noted in the test group; however, bone regeneration was seen only at areas adjacent to a bony wall of the defect. The mean bone-to-implant contact was 27.6 ± 19.1% (control group) versus 6.8 ± 7.9% (test group). The mean bone area percentage was 11.8 ± 10.1% (control group) versus 6.8 ± 6.9% (test group). Implant survival was 100% at 6 months for both the groups. It was concluded that although the use of a PCL–TCP scaffold showed better maintenance of the alveolar contour as compared to autogenous particulate bone at 6 months, there was minimal bone regeneration within the defect.